Cultural Sensitivity Exploration: Client Experiences with The Therapeutic Community Method at The National Narcotics Agency Rehabilitation Center - Roy Hardi Siahaan (Publikasi Indonesia, 2024)
Drug abuse is one of the major challenges in global society. Data in the World Drug Report issued by UNODC shows that around 292 million people in the world will use drugs in 2024. The significant impact of this occurs in the younger generation. This study aims to analyze the experiences of clients undergoing inpatient rehabilitation at the Rehabilitation Center of the National Narcotics Agency (BNN) Indonesia using the Therapeutic Community (TC) method. This method facilitates social interaction and learning from shared experiences in an environment that supports the recovery process. Through semi-structured interviews with six clients from various provinces, this study found that cultural sensitivity plays an important role in increasing the effectiveness of rehabilitation. Clients can find their identity, form close relationships with fellow residents based on similar backgrounds, and understand diversity in the community. However, challenges arise from cultural differences that sometimes clash with TC values, requiring adaptation and understanding among clients. The results of the study indicate that the TC method at the BNN Rehabilitation Center was derived not only to contribute to the reduction of maladaptive behavior, but also to encourage the development of communication skills, emotional management, and independence. Although clients feel many benefits from the rehabilitation process, there is a need to increase recreational activities to prevent boredom. This study recommends the need for a more inclusive approach in understanding the cultural diversity of clients for more optimal results in drug rehabilitation.